(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
Abstract: The purpose of this article is to shed light on charles de foucauld’s mission in the saoura, the tidikelt, and the hoggar regions of algeria between 1901 and 1916. The method of research in this article relies on collecting and comparing data from different french sources, mainly foucauld’s correspondences. This article puts into evidence the fact that charles de foucauld failed in his mission in converting the autochthons into christianity. He was military by profession and actively participated in the french invasion of the algerian sahara, which in the end cost him his life in 1916. The findings in this article imply that much has to be reconsidered and studied in order to reveal the true history of the algerian sahara and the impact of the french presence there. Keywords: charles de foucauld, -missionary, -algerian sahara, -french colonisation, -senoussists, -world war i ملخص: الغرض من هذا المقال هو إلقاء الضوء على المهمة التبشيرية لشارل دي فوكو في الصحراء الجزائرية من 1901 إلى 1916. تعتمد طريقة البحث الواردة في هذه المقالة على جمع ومقارنة البيانات من مصادر فرنسية مختلفة و بشكل رئيسي مراسلات دي فوكو. يوضح هذا المقال حقيقة أن شارل دي فوكو لم يفلح في مهمته التبشيرية إذ واجهته صعوبات كثيرة و رفض قاطع لمحاولاته إدخال السكان المحليين في الدين المسيحي. لقد كانت صفته العسكرية تغلب كثيراً عن صفته التبشيرية بحيث أنه شارك بنشاط في الغزو الفرنسي للصحراء الجزائرية، والذي كلفه في النهاية حياته عام 1916. و تشير النتائج الواردة في هذا المقال إلى أن الكثير من الوقائع التاريخية يجب إعادة النظر فيها عن طريق الدراسة الأكاديمية من أجل الكشف عن التاريخ الحقيقي للصحراء الجزائرية وتأثير الوجود الفرنسي فيها الكلمات الدالة: شارل دي فوكو ، التبشير ، الصحراء الجزائرية . الاستعمار الفرنسي ، السنوسين ، الحرب العالمية الأولى